Burden of Pertussis in COPD: A Retrospective Database Study in England. (7th March 2021) - Aris, Emmanuel; Harrington, Lauriane; Bhavsar, Amit; Simeone, Jason C.; Ramond, Anna; Papi, Alberto; Vogelmeier, Claus F.; Meszaros, Kinga; Lambrelli, Dimitra; Mukherjee, Piyali
Abstract: Chronic obstructive pulmonary disease (COPD) may increase the risk and severity of pertussis infection. Health care resource utilization (HCRU) and direct medical costs (DMC) of treating pertussis among patients with COPD are unknown. Reported incidence of pertussis among individuals aged ≥ 50 years with COPD was assessed in Clinical Practice Research Datalink and Hospital Episode Statistics databases during 2009–2018 using a retrospective cohort design. HCRU and DMC from the National Health Service perspective were compared between patients with COPD and pertussis and propensity score-matched patients with COPD without pertussis. Seventy-eight new pertussis events were identified among 387 086 patients with COPD aged ≥ 50 years (incidence rate: 4.73; 95% confidence interval 3.74–5.91 per 100 000 person-years). HCRU and DMC were assessed among 67 patients with COPD and pertussis and 267 matched controls. During the month before the pertussis diagnosis, the rates of general practitioner (GP)/nurse visits (4289 vs. 1774 per 100 patient-years) and accident and emergency visits (182 vs. 18 per 100 patient-years) were higher in the pertussis cohort; GP/nurse visits (2935 vs. 1705 per 100 patient-years) were also higher during the following 2 months (all p  < 0.001). During the month before the pertussis diagnosis, annualized per-patient total DMC were £2012 higher in the pertussis cohort (£3729 vs. £1717; p  < 0.001); during the following 2 months, they were £2407 higher (£5498 vs. £3091; p  < 0.001). In conclusion, a pertussis episode among individuals with COPD resulted in significant increases in HCRU and DMC around the pertussis event.